Structure of the effector-binding domain of the arabinose repressor AraR from Bacillus subtilis - Procházková, Kateřina; Cermáková, Kateřina; Pachl, Petr; Sieglová, Irena; Fábry, Milan; Otwinowski, Zbyszek; Rezáčová, Pavlína (Acta crystallographica. Section D, Biological crystallography, 2012)
In Bacillus subtilis, the arabinose repressor AraR negatively controls the expression of genes in the metabolic pathway of arabinose-containing polysaccharides. The protein is composed of two domains of different phylogenetic origin and function: an N-terminal DNA-binding domain belonging to the GntR family and a C-terminal effector-binding domain that shows similarity to members of the GalR/LacI family. The crystal structure of the C-terminal effector-binding domain of AraR in complex with the effector L-arabinose has been determined at 2.2 Å resolution. The L-arabinose binding affinity was characterized by isothermal titration calorimetry and differential scanning fluorimetry; the K(d) value was 8.4 ± 0.4 µM. The effect of L-arabinose on the protein oligomeric state was investigated in solution and detailed analysis of the crystal identified a dimer organization which is distinctive from that of other members of the GalR/LacI family.
Keywords: bakteriální proteiny; Arabinose; vazba proteinů; Bacterial Proteins; Models, Molecular; Bacillus subtilis; terciární struktura proteinů; Crystallography, X-Ray; molekulární modely; Repressor Proteins; Protein Structure, Tertiary; Protein Binding; arabinosa; represorové proteiny; krystalografie rentgenová